Michel Houellebecq in Lithuanian: The Paradoxes of Translation - Černiuvienė, Liucija; Jakutytė, Rūta (Literatūra, 2019)
The article analyses all five published translations to Lithuanian language of Michel Houellebecq’s novels (The Elementary Particles, Platform, The Possibility of an Island, The Map and the Territory and Submission) with a focus on translation of obscene and profane language. First, the usage of obscene and profane language for stylistic purposes in the context of entire Houellebecq’s literary creation is reviewed, based on the works about the author by literary translators, literary critics and translators of Houellebecq’s books from France, Switzerland and Brazil. After determining that obscene and profane language is one of the keys to the meaning of Houellebecq’s work and discussing peculiarities of the usage of such language in Lithuania (censorship, self-censorship, taboo), the translation analysis of the novels is presented. Such translation methods as exact translation, euphemisation, neutralisation and omitting were reviewed. After completing a qualitative analysis, it was established that Lithuanian translators clearly avoid using obscene and profane language and rather choose euphemisation, neutralisation or omission. The results of the qualitative analysis presented in the article confirm this tendency: overall, approximately 50 percent of all obscene and profane Houellebecq’s language was replaced with euphemisms, neutralised or omitted. Translation mistakes and inaccuracies were not separately analysed in this article, therefore were not presented in percentage terms. After completing the research, it can be stated that the translations of Houellebecq’s novels to Lithuanian language significantly lack in meaning and it would not be appropriate to discuss Houellebecq’s works in the literary discourse after reading them only in Lithuanian language. Moreover, a faulty tendency of translating each author’s book by a different translator is present in Lithuania, resulting in distortion of author’s style. Therefore, literary paradoxes of Houellebecq (according to Bruno Viard) result in paradoxes in translation to Lithuanian language: obscene and profane language still remains a certain sociocultural taboo, and one appropriate novel’s translation (The Possibility of an Island) out of five does not change the essence of the issue because the remaining four do not reflect author’s style and chosen registers. Translators must respect the will of a writer and refuse to translate the work if it presents an issue in terms of their sense of morality and ethics.